Mechanism of azimuthal mode selection in two-dimensional coaxial Bragg resonators - Ginzburg, N; Peskov, N; Sergeev, A; Zaslavsky, V; Konoplev, I; Fisher, L; Ronald, K; Phelps, A; Cross, A; Thumm, M (2009)
The analysis of electrodynamic properties of two-dimensional (2D) Bragg resonators of coaxial geometry realizing 2D distributed feedback was carried out using a quasioptical approach of coupled-wave theory and three-dimensional (3D) simulations. It is shown that the high selectivity of a 2D Bragg resonator over the azimuthal index originates from the topological difference in the dispersion diagrams of the normal symmetrical and nonsymmetrical waves near the Bragg resonance frequency in a double-periodic corrugated unbounded waveguide. For a symmetrical mode near the Bragg frequency it was found that the group velocity tends to zero as well as its first derivative. This peculiarity of the dispersion characteristic provides the conditions for the formation of an eigenmode with a Q -factor essentially exceeding the Q -factors of other modes. The results of the theoretical analysis coincide well with results of 3D simulations using the CST code "MICROWAVE STUDIO" and confirm the high azimuthal selectivity of the system. © 2009 American Institute of Physics.